1961
DOI: 10.1080/17470216108416476
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting and Perceptual Learning

Abstract: Filial responses are first considered by reference to the initial stimulus situations. Findings on variability in responsiveness of chicks are reported and discussed. Facilitated responsiveness subsequent to visual stimulation is reported. The concept of critical period is examined in the light of other workers’ and our own findings; it is concluded that imprinting ends as a result of its own action rather than through the effects of fear. Following responses are further considered by reference to the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
1
1

Year Published

1968
1968
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(58 citation statements)
references
References 28 publications
5
50
1
1
Order By: Relevance
“…Thus, during the initial imprinting session, already establishedattachment behaviors directed toward siblings may interfere with the emissionof filial behavior. Consistent with this account, both Guiton (1959) and Sluckin and Salzen (1961) observed that isolating group-reared birds for several hours prior to imprinting resulted in an increase in their subsequent following of the imprinting stimulus. Similarly, Hoffman (1968) found that ducklings confronted as a group with an imprinting stimulus appeared to ignore the stimulus.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Thus, during the initial imprinting session, already establishedattachment behaviors directed toward siblings may interfere with the emissionof filial behavior. Consistent with this account, both Guiton (1959) and Sluckin and Salzen (1961) observed that isolating group-reared birds for several hours prior to imprinting resulted in an increase in their subsequent following of the imprinting stimulus. Similarly, Hoffman (1968) found that ducklings confronted as a group with an imprinting stimulus appeared to ignore the stimulus.…”
supporting
confidence: 54%
“…One factor may be the choice of an imprinting stimulus. Most of the studies that have failed to demonstrate strong imprinting have used silent-moving mechanical stimuli (Graves & Siegel, 1968;Guiton, 1959;James, 1960;Sluckin & Salzen, 1961), while studies that have succeeded in demonstrating imprinting generally have employed more complex stimuli (Polt & Hess, 1964;Smith & Bird, 1964; the present research; but see Hoffman, 1968).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…There are thus "inhibitory effects of socialization on the following response to unfamiliar objects." A similar conclusion was presented by Sluckin & Salzen (1961) who stated that with increased imprinting "the bird becomes less likely to respond to stimuli other than the experienced one or ones." In accordance with the above conclusions, it has been shown that the "critical period" during which stimulus exposure can elicit following behavior can be significantly lenghtened if the bird is deprived of visual and/or social experience after hatching (Moltz & Stettner, 1961;Sluckin, 1962).…”
supporting
confidence: 49%
“…This, in turn, raises a final and related issue. Investigators employing an imprinting stimulus commonly assume that this stimulus is serving as a mother surrogate (e.g., Hess, 1973;Hinde, 1974;Hoffman & Ratner, 1973;Sluckin, 1965;Sluckin & Salzen, 1961). The present research, however, emphasizes the need to critically examine the relationship between imprinting stimuli and natural social companions in a young bird's environment-mother, siblings, potential mate, or whatever.…”
Section: Discussionmentioning
confidence: 95%